Affirmative Action: Reservation Seats untuk Perempuan di Parlemen India - Evi Yunita Kurniaty (Universitas Medan Area, 2015)
The study aims to help us understand and analyze women's efforts in the policy-making process to increase their political participation in the constitutional and electoral processes. We can also see the extent to which the values rooted in the patriarchal culture in a society and what can be done and reduce them. Affirmative action is carried out in India by applying the system of reservation seats for women in the Indian Parliament. This is done in India is proven to increase the number of women in the Indian Parliament. By the way there are quotas for women as a strategy for accessing the political arena has growing support among MPs. In this study, Indonesia could get a reservation seats of learning about the system is done. To increase the representation in the